SOCIAL PSYCHOLOGY OF ALTURISM AND ALTHURISTIC BEHAVIOR - Alijanov Nurbek (Journals Park Publishing, 2023)
The article talks about the concept of altruism, characteristics, characters and social psychological research of altruistic behavior, research of altruistic behavior in a broad sense, and practical application of the obtained results.
Keywords: alturism, altruistic behavior, empiric, prosocial behavior, character, criterion.